Research Progress on the Application of Lignin Nanoparticles in Composite Film Materials - Page, Sean; Nomura, Richal; Cairney, Michael; Willan, Daniel (Journal of Green Energy and Environmental Engineering, 2024)
This article provides a detailed introduction to various preparation methods of lignin nanoparticles (LNPs), including self-assembly, mechanical methods, and interfacial polymerization/cross-linking, etc. The review weighs the merits and limits of common film-forming biopolymers—PVA, PLA, chitosan, pectin and starch—and explains how nanoscale lignin acts as a natural reinforcement that boosts strength, blocks UV and curbs water vapor, before outlining the road ahead for fully bio-based packaging.